2022
DOI: 10.1371/journal.pone.0264688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flow diverter stent malposition on intracranial aneurysm hemodynamics—An experimental framework using stereoscopic particle image velocimetry

Abstract: Background Flow-diverting stents are increasingly used for the minimally-invasive treatment of intracranial aneurysms. However, a correct positioning of such devices can be challenging due to varying vessel diameters as well as the complex anatomy of the neurovasculature. As a consequence, unsuccessful treatment outcomes are increasingly reported requiring an improvement of the understanding of stent-induced flow modification. Methods To evaluate the effect of different degrees of flow diverter stent malposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This finding is in line with a previous study in which OVI increased inside the IA after implanting an FDS. 31 Roloff et al 31 found that FDS malpositioning increases OSI, but has no major effect on flow reduction. This leads to the assumption that adequate positioning of the Contour could ensure a decrease in OSI/OVI ( figures 3 and 4 , table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with a previous study in which OVI increased inside the IA after implanting an FDS. 31 Roloff et al 31 found that FDS malpositioning increases OSI, but has no major effect on flow reduction. This leads to the assumption that adequate positioning of the Contour could ensure a decrease in OSI/OVI ( figures 3 and 4 , table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that the stent porosity is influenced by the geometry of the aneurysm. However, the FDS porosity can also be influenced by the way the FDS is deployed in the vessel (Roloff & Berg 2022).
Figure 12.( a ) Stent geometries for two aneurysm models reconstructed from synchrotron X-ray micro-tomography images.
…”
Section: Comparison Of Haemodynamics Before and After Fds Treatmentmentioning
confidence: 99%
“…These results demonstrate that the stent porosity is influenced by the geometry of the aneurysm. However, the FDS porosity can also be influenced by the way the FDS is deployed in the vessel (Roloff & Berg 2022). The fact that the treatment is not efficient enough at reducing the flow in the sac is a combination of two factors: first, before treatment the inflow in the sac was high (i.e.…”
Section: Effect Of Fds Porositymentioning
confidence: 99%
See 2 more Smart Citations